2019
DOI: 10.1177/0145721719889338
|View full text |Cite
|
Sign up to set email alerts
|

Individual-, Community-, and Health System–Level Barriers to Optimal Type 2 Diabetes Care for Inner-City African Americans: An Integrative Review and Model Development

Abstract: Purpose The purpose of this integrative review is (1) to elucidate the unique barriers faced by inner-city African Americans for type 2 diabetes (T2DM) care; (2) to identify effective interventions/programs for optimal T2DM care at the individual, community, and health systems levels; and (3) to integrate 2 behavioral models and 1 social ecological model for framing interventions for inner-city African American to optimize T2DM care. Methods PRISMA guidelines were followed to systematically search PubMed, Psyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 67 publications
0
24
0
Order By: Relevance
“…It is essential to promote access to DSMES services by identifying and addressing population barriers and health inequities (3). Barriers may include socioeconomics, cultural factors, misaligned schedules, health insurance shortfalls, perceived lack of need, or limited encouragement from healthcare professionals to engage in DSMES (28, 44,45). SDOH related to the target population should guide service design and delivery (46).…”
Section: Standard 2: Population and Service Assessmentmentioning
confidence: 99%
“…It is essential to promote access to DSMES services by identifying and addressing population barriers and health inequities (3). Barriers may include socioeconomics, cultural factors, misaligned schedules, health insurance shortfalls, perceived lack of need, or limited encouragement from healthcare professionals to engage in DSMES (28, 44,45). SDOH related to the target population should guide service design and delivery (46).…”
Section: Standard 2: Population and Service Assessmentmentioning
confidence: 99%
“…Specific for inner-city African Americans, an integrative review exploring the barriers across the individual, community, and health system levels found that across 46 studies, 2 focused on quality of life as an outcome for diabetes. 21 The current findings suggest that quality of life should be considered more frequently as a patient-reported outcome and that factors at the individual, community, and health system levels should be incorporated into interventions to improve quality of life among inner-city African Americans with diabetes.…”
Section: Implications For Diabetes Care and Education Specialistsmentioning
confidence: 86%
“…Drawn from a social ecological model, this recently published framework was developed based on integration of 2 behavioral frameworks for diabetes and informed by the literature on diabetes outcomes for inner-city African Americans. 21 This conceptual framework was used to select measured variables for inclusion in this study that represent barriers for inner-city African Americans with type 2 diabetes across the individual, community, and health systems levels. All measures selected have been previously validated and cited according to published validation.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Frameworks such as the chronic care model clearly indicate that health care does not occur in a vacuum and recent work has shown that individual, community and health systems factors are important drivers of diabetes outcomes. 46 Therefore, as diabetes care moves away from traditional models of care, outward facing interventions using public health approaches are greatly needed to address the role that neighborhood factors are playing on diabetes management and outcomes. For example, a number of public sector and community-based efforts have demonstrated that violence and crime can be reduced in communities by improving connectivity, 47,48 developing and expanding green space across communities and surrounding vacant lots, 47,48 and safe ride programs.…”
Section: Discussionmentioning
confidence: 99%